2016
DOI: 10.1111/ped.12928
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p38 mitogen‐activated protein kinase (p38MAPK) and pathological change in intussusception

Abstract: The present mouse model can be used to assess the dynamic pathological changes associated with intussusception. I/R is associated with upregulation of p38MAPK in intussusception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Growing evidence demonstrates that the p38MAPK family plays an important role in intracellular signal transduction in response to extracellular stimuli, including intestinal I/R challenge (Fu, Xing, et al, 2003;Fu, Yang, et al, 2003;Guo et al, 2016;Li et al, 2021;Li, Xu, et al, 2017;Liu et al, 2020;Ming et al, 2019;Murayama et al, 2006;Santén et al, 2009;Yusof et al, 2009;Zheng et al, 2005). Dexmedetomidine (Liu et al, 2020), propofol (Li et al, 2021), and 6-gingerol (Li, Xu, et al, 2017) have been shown to protect against intestinal I/R injury via p38MAPK inhibition, wherein p38MAPK activation conferred detrimental effects on intestinal I/R progression.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence demonstrates that the p38MAPK family plays an important role in intracellular signal transduction in response to extracellular stimuli, including intestinal I/R challenge (Fu, Xing, et al, 2003;Fu, Yang, et al, 2003;Guo et al, 2016;Li et al, 2021;Li, Xu, et al, 2017;Liu et al, 2020;Ming et al, 2019;Murayama et al, 2006;Santén et al, 2009;Yusof et al, 2009;Zheng et al, 2005). Dexmedetomidine (Liu et al, 2020), propofol (Li et al, 2021), and 6-gingerol (Li, Xu, et al, 2017) have been shown to protect against intestinal I/R injury via p38MAPK inhibition, wherein p38MAPK activation conferred detrimental effects on intestinal I/R progression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TLR4 can activate the MAPK and NF-kB pathways, which are critical regulators of the inflammatory response, cell survival, and apoptosis [ 3 ]. We previously observed high p38 MAPK expression in response to I/R injury [ 18 ]. Additionally, Ben et al demonstrated that TLR4 plays an important role in acute lung injury following intestinal ischemia [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAK-242 (3 mg/kg), a specific inhibitor of TLR4, was administered intraperitoneally 60 min prior to intussusception. Intussusception was established under ether inhalation anesthesia as described previously [ 18 ]. Intussusception was observed in all mice in the I/R injury and TAK-242 groups after 60 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal ischemia-reperfusion injury (I/R) can occur during pediatric intussusception [3,4], and any delay in diagnosis or treatment can lead to loss of intestinal viability that requires bowel resection [5,6].…”
Section: Introductionmentioning
confidence: 99%